2011
DOI: 10.1177/1362361311411935
|View full text |Cite
|
Sign up to set email alerts
|

Confusion and inconsistency in diagnosis of Asperger syndrome: a review of studies from 1981 to 2010

Abstract: This paper presents a review of past and current research on the diagnosis of Asperger syndrome (AS) in children. It is suggested that the widely used criteria for diagnosing AS in the Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV are insufficient and invalid for a reliable diagnosis of AS. In addition, when these diagnostic criteria are applied, there is the potential bias of receiving a diagnosis towards the high-functioning end of the autism spectrum. Through a critical review of 69 researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 85 publications
1
29
0
2
Order By: Relevance
“…On the contrary, Sharma et al [17 ■■ ] reviewed 69 studies published over two decades on Asperger’s syndrome and concluded that, because of the overlapping signs and symptoms relative to autistic disorder, the DSM-IV criteria were insufficient and invalid. A multisite study including over 2000 individuals all carefully diagnosed with gold standard diagnostic instruments by Lord et al [18 ■■ ,19] suggested that the diagnosis of Asperger’s disorder was more significantly influenced by where one was evaluated than by the symptoms with which one presented.…”
Section: Dsm-5mentioning
confidence: 99%
“…On the contrary, Sharma et al [17 ■■ ] reviewed 69 studies published over two decades on Asperger’s syndrome and concluded that, because of the overlapping signs and symptoms relative to autistic disorder, the DSM-IV criteria were insufficient and invalid. A multisite study including over 2000 individuals all carefully diagnosed with gold standard diagnostic instruments by Lord et al [18 ■■ ,19] suggested that the diagnosis of Asperger’s disorder was more significantly influenced by where one was evaluated than by the symptoms with which one presented.…”
Section: Dsm-5mentioning
confidence: 99%
“…However, more subtle characteristics in the nature of social interaction, motor skills and speech patterns that since Asperger's first description have differentiated AD from autism, are not acknowledged in the new DSM-5 ASD criteria [35]. Positive aspects of autism, such as savant skills, are neglected as well [36].…”
Section: Introductionmentioning
confidence: 99%
“…For some this created confusion as it did not allow clear demarcation of AS, while for others it marked the need for additional discriminators such as motor function and neuropsychological profiling. Individuals with AS are said to have a higher probability of presenting with motor difficulties (clumsiness), and some groups, though not all, have also reported that they are more likely to show a non-verbal learning disability profile in contrast to those with an HFA diagnosis of similar overall cognitive ability [17]. AS is therefore often diagnosed later than other ASDs, (after age three or so) [18].…”
Section: Distinction From Other Asdsmentioning
confidence: 99%